Future perspectives on food supply in developing countries - Pinstrup-Andersen, Per (SAGE Publications, 1993)
Dramatic increases during the 1980s in agricultural production, particularly in the developing world, are due to both the increased area under cultivation and growth in yields per unit area. However, growth in food production has failed to keep pace with population growth in the majority of countries surveyed, and especially in Africa. Changes in rural infrastructure, agricultural technology, environmental management and government policy will influence food production in the future, while food consumption patterns in developing countries will change as a result of population growth, urbanization and changing lifestyles. Shortfalls are likely to occur, especially in Africa, where the availability of new land for cultivation is declining. The pressures on food production will rise, unless efforts are increased to reduce population growth.